2022
DOI: 10.1002/prm2.12062
|View full text |Cite
|
Sign up to set email alerts
|

Renal hydatid cyst mimicked cystic renal cell carcinoma: A case report

Abstract: Hydatid cyst (HC) is a zoonotic parasitic disease in agricultural and pastoral areas while renal involvement without liver and lung hydatid is both less common in clinical practice and rarely described in literature. We present a case of a 40‐year‐old male from Xinjiang who complained of flank pain in the right with oliguria. Robot‐assisted laparoscopic exploration, conversion to open laparotomy and excision of internal capsule in right kidney were performed. Finally, a typical renal HC was diagnosed after com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 19 publications
0
1
0
Order By: Relevance
“…To the Editor, I read the latest case report of Wei et al with great interest which published in your journal in June, 2022. 1 Authors reported an interesting hydatid cyst case which mimicked malignant cancer. Interestingly, hydatid cyst really mimics other clinical conditions.…”
mentioning
confidence: 99%
“…To the Editor, I read the latest case report of Wei et al with great interest which published in your journal in June, 2022. 1 Authors reported an interesting hydatid cyst case which mimicked malignant cancer. Interestingly, hydatid cyst really mimics other clinical conditions.…”
mentioning
confidence: 99%